INTERACTION OF CODES IN SUBCULTURE JARGON: (A CASE STUDY OF “FORMULA-1” FANS' SOCIOLECT) (Philological Studies, 2019)
At the present day, the cultural diversity is realized not only through ethnic features, but also through subcultural ones. Subcultures are particular units within the dominant culture. Subcultures are based on three components: the social stratum, social stereotypes and values, the language (jargon or sociolect). The article discusses the sociolect of Formula One fans. It is shown that this sociolect is a complex, “mixed” language that not only generates the required lexical units, but also uses several terminological systems, jargons, and colloquial speech elements as sources. The complexity of the sociolect is determined by the type of activity that is characterized the subculture. It is obvious that not only this sociolect, but other subcultures sociolects are characterized as complex, “mixed” languages.
Keywords: subculture, sociolect, lexical units, codes, interaction, Formula One